2018
DOI: 10.5539/ijel.v8n5p10
|View full text |Cite
|
Sign up to set email alerts
|

Teachers and Technology: Trends in English Language Teaching in Saudi Arabia

Abstract: Technology has impacted the learning approaches and vice-versa with an aim to improve the standards of language teaching/learning process. The present study focuses on teachers' preferences and use of technology in their language classrooms. A survey was conducted to seek opinion of EFL teachers both male and female at the English language center on technology-related competencies. The survey comprised four domains: planning and preparation, classroom management, instruction, and professional responsibilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…The Saudi teaching cadre spends more time preparing and actualizing online courses, leading to job dissatisfaction and frustration. This time factor also has a detrimental impact on learners if not handled appropriately in online learning (Farooq & Soomro, 2018).…”
Section: Preparation Deficiencymentioning
confidence: 99%
“…The Saudi teaching cadre spends more time preparing and actualizing online courses, leading to job dissatisfaction and frustration. This time factor also has a detrimental impact on learners if not handled appropriately in online learning (Farooq & Soomro, 2018).…”
Section: Preparation Deficiencymentioning
confidence: 99%
“…Menurut Budiman et al, (2018), praktik guru dalam pemanfaatan teknologi mempunyai hubungan yang erat dengan bagaimana guru mempersepsikan teknologi. Beberapa peneliti sebelumnya telah mendiskusikan dan memfokuskan penelitian mereka kepada persepsi guru terhadap pemanfaatan teknologi di dalam pembelajaran (Almunawwarah, 2014;Bilal & Saeed, 2015;Djiwandono, 2019;Farooq & Soomro, 2018;Jatileni & Jatileni, 2018;Jimoyiannis & Komis, 2007;Juliana & Muslem, 2017;Soko, 2017). Sebagian besar temuan dalam beberapa penelitian tersebut mengindikasikan bahwa para guru memiliki pandangan yang baik terhadap manfaat mengintegrasikan teknologi dalam pembelajaran.…”
Section: Pendahuluanunclassified
“…The study also showed some differences in teacher preparation for using technology. Farooq and Soomro (2018) surveyed the opinions of EFL 100 teachers at the English language center in Taif University on technology-related competencies. The survey included four domains: planning and preparation, classroom management, classroom instruction, and professional duties.…”
Section: Related Literature Ict In Saudi Educational Systemmentioning
confidence: 99%